Silibinin attenuates high-fat diet-induced renal fibrosis of diabetic nephropathy - Liu K; Zhou S; Liu J; Wang Y; Zhu F; Liu M (Dove Medical Press, 2019)
Kun Liu,1,* Shiju Zhou,1,* Jinyan Liu,1,2 Yingying Wang,1 Fengxian Zhu,1 Man Liu11Department of Nephrology, Jining No. 1 People’s Hospital, Jining 272000, Shandong, People’s Republic of China; 2Department of Nephrology, Jining Medical University, Jining 272000, Shandong, People’s Republic of ChinaCorrespondence: Jinyan LiuDepartment of Nephrology, Jining No. 1 People’s Hospital, No. 6 Jiankang Road, Jining 272000, Shandong, People’s Republic of ChinaTel +86 0 537 225 3104Email jinyanliu32@126.com*These authors contributed equally to this workAim: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease. Silibinin is a flavonoid compound which has medicinal value. Previous studies revealed that silibinin exhibited an anti-fibrotic effect. However, whether silibinin could attenuate high-fat diet (HFD)-induced renal fibrosis remains unclear. Therefore, this study aimed to explore the molecular mechanism by which silibinin regulated renal fibrosis induced by HFD.Methods: In the present study, human renal glomerular endothelial cells (HRGECs) were treated with various concentrations of silibinin. Then, cell viability and apoptosis were measured by MTT assay and flow cytometry, respectively. In addition, HRGECs were exposed to 100 nM TGF-β1 for mimicking in vitro renal fibrosis. The expressions of collagen I, fibronectin, and α-SMA were detected by reverse transcription-quantitative polymerasechain reaction and Western blot. Protein levels of p-IκB and p-p65 were examined by Western blot; meanwhile, level of NF-κB was measured by immunofluorescence staining. Furthermore, HFD-induced mouse model of renal fibrosis was established. The mouse body weight, fasting glucose, kidney weight/body weight, microalbuminuria, kidney histopathology, and fibrotic area were measured to assess the severity of renal fibrosis.Results: Low concentration of silibinin (≤50 μM) had no cytotoxicity, while high concentration of silibinin (≥75 μM) exhibited significant cytotoxicity. Additionally, TGF-β1 increased the expressions of collagen I, fibronectin, α-SMA, p-IκB, and p-p65 and decreased the level NF-κB, while these effects were notably reversed by 50 μM silibinin. Moreover, both 50 and 100 mg/kg silibinin greatly decreased HFD-induced the upregulation of kidney weight/body weight, microalbuminuria, and fibrotic area. 100 mg/kg silibinin markedly reduced collagen I, fibronectin, and p-p65 expressions in mice renal tissues.Conclusion: Silibinin was able to attenuate renal fibrosis in vitro and in vivo via inhibition of NF-κB. These data suggested that silibinin may serve as a potential agent to alleviate the renal fibrosis of DN.Keywords: silibinin, renal fibrosis, diabetic nephropathy, high-fat diet, TGF-β1, NF-κB pathway